2021
DOI: 10.3389/fphar.2021.733526
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Tailored Isotretinoin Treatment in Moderate to Severe Acne: Real-Life Data

Abstract: This retrospective single-center study analyzes the efficacy and safety of isotretinoin for the treatment of moderate to severe acne in real-life clinical practice, particularly with regard to acne severity, isotretinoin cumulative dosage, and patients’ gender. The results suggest the opportunity of an early isotretinoin systemic treatment in patients affected by moderate acne and emphasize the importance of an appropriate dose adjustment in order to minimize adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
(17 reference statements)
0
8
0
2
Order By: Relevance
“…16,22,23 Therefore, recent studies have concluded that individual conditions should be considered when designing treatment protocols for moderate acne. 16,24 However, the current prescription still fails to take into account different gradations of the severity of moderate acne. Our study identifies acne grading scores as an important factor in designing a treatment protocol for moderate acne which could be useful for clinicians to individualize treatment dose based on patient's conditions.…”
Section: Results For Side-effects and Patient Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,22,23 Therefore, recent studies have concluded that individual conditions should be considered when designing treatment protocols for moderate acne. 16,24 However, the current prescription still fails to take into account different gradations of the severity of moderate acne. Our study identifies acne grading scores as an important factor in designing a treatment protocol for moderate acne which could be useful for clinicians to individualize treatment dose based on patient's conditions.…”
Section: Results For Side-effects and Patient Satisfactionmentioning
confidence: 99%
“…However, treatment outcomes have varied widely from one study to another even when using the same therapy regimen 16,22,23 . Therefore, recent studies have concluded that individual conditions should be considered when designing treatment protocols for moderate acne 16,24 . However, the current prescription still fails to take into account different gradations of the severity of moderate acne.…”
Section: Discussionmentioning
confidence: 99%
“…The high cumulative dose is adversely associated with an increased risk of OI side effects and poor medication adherence. 32 Moreover, neither daily dosage nor cumulative dose influenced acne relapse as long as treatment continued for ≥2 months after the acne had completely resolved. 33 These contradictory findings support the concept of extending OI (at least 1 month) after complete clearance of acne.…”
Section: Discussionmentioning
confidence: 97%
“…The high cumulative dose is adversely associated with an increased risk of OI side effects and poor medication adherence. 32 Moreover, neither daily dosage nor cumulative dose influenced acne relapse as long as treatment continued for ≥2 months after the acne had https://doi.org/10.2147/JMDH.S405509…”
Section: Discussionmentioning
confidence: 99%
“…В большинстве случаев встречается персистирующее акне, которое наблюдается у 73,2-82% женщин со взрослым акне [11,[14][15][16][17][18]. Акне с поздним началом встречается гораздо реже -у 20-40% женщин [8,19,20].…”
Section: типы течения акнеunclassified